Pengaruh penggunaan tepung ubi jalar ungu sebagai pengganti tepung terhadap kualitas sosis daging ayam broiler - Abertus Nino; Pieter R. Kale; Yacob Robert Noach (Jurnal Peternakan Lahan Kering, 2019)
This experiment goals determined to know the effect of using purple potatos flour as subtitute of tapioca on broiler chicken sausage. The used in this experiment were broiler meat, purple potatto, tapioca, onion, garlic, salt, skim milk, pepper, and nutmeg. This research using the Completelly Random Design (CRD), was with 5 treatments and 4 replications was applied in this experiment. Those threatment were, P0 = Control of purple potatto 0% (tapioca 100%), P1 = The thing sausage make use of purple potatto 25% + tapioca 75%, P2 = The thing sausage make use of purple potatto 50% + tapioca 50%, P3= The thing sausage make use of purple potatto 75% + tapioca 25%, P4= The thing sausage make use of purple potatto 100% (tapioca 0%). The parameters observed included antioxidant, proteins, fat, organoleptic (color, taste, and texture). Result showed that, the threament have close significant effect (P<0.01) on the antioxidant, proteins, color, taste and texture and not no significant effect on fat content (P>0.05) to decrease the fat of broiler sausage. It can be conclude that, using of purple potatos flour in 25-100% level maight be increase the antioxidant and protein but decrease of fat of broiler sausage.